2013
DOI: 10.1016/j.aju.2012.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Free-flank modified supine vs. prone position in percutaneous nephrolithotomy: A prospective randomised trial

Abstract: ObjectiveTo compare the technical aspects, operative time, safety and effectiveness of percutaneous nephrolithotomy (PCNL) in the free-flank modified supine position (FFMSP) vs. the standard prone position (SPP).Patients and methodsSeventy-seven patients (47 men and 30 women) with renal stones were enrolled and systematically randomised into two groups, A (39 patients) treated using the FFMSP, and B (38 patients) in the SPP. The outcome was considered as a cure (successful procedure) if the patient became ston… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 20 publications
0
3
1
Order By: Relevance
“…Abdel-Mohsen et al, [30] in contrast to our results, compared the technical aspects, operative time, safety and effectiveness of PCNL in the supine position vs. the standard prone position. They found no significant difference between the studied groups as regards fluoroscopy time and patients outcome.…”
Section: Discussioncontrasting
confidence: 67%
“…Abdel-Mohsen et al, [30] in contrast to our results, compared the technical aspects, operative time, safety and effectiveness of PCNL in the supine position vs. the standard prone position. They found no significant difference between the studied groups as regards fluoroscopy time and patients outcome.…”
Section: Discussioncontrasting
confidence: 67%
“…The results indicated that our average fluoroscopy time was 271.70 seconds (about 4.5 minutes), with the fastest being 10 seconds and the slowest being 45 minutes. Compared to previous studies that used C-arm support like Mohamed M. Abdallah 11 and Abdel-Mohsen Essam 12 with an average fluoroscopy time of 8.3 and 6.5 minutes respectively, our time was probably faster due to the pre-calculated position and depth of the needle based on CTscan. As a result, both the surgical and radiation exposure times were significantly reduced.…”
Section: Discussionmentioning
confidence: 73%
“…(2013), who compared the technical aspects, operative time, safety, and effectiveness of PCNL in the supine position versus the standard prone position. [ 10 ] They found no significant difference between the studied groups in fluoroscopy time and patients’ outcome. Ozdemir et al .…”
Section: Discussionmentioning
confidence: 94%